Strategic decision making in the arts : case studies in arts and cultural entrepreneurship - Beckman, Gary D., 1961-; Androes, Karl (Discovering the creative industries, 2025)
"For entrepreneurs in the creative fields, decision making is both a necessity and an art. Applying creativity to strategic decisions requires skills developed over time. This textbook provides arts entrepreneurship students a series of case studies centering on decision-making models applicable to launching and sustaining arts businesses. Each case set in the book focuses on a particular arts entrepreneur within the context of a range of creative businesses, from performance to videography. To facilitate classroom adoption, the authors provide expert guidance on getting the most from case-study-based learning. Additional features include insights into the key decision-making models in each case, analysis by a leader in the arts entrepreneurship education field on the factors forcing a decision, and a broad view on the arts ecologies surrounding each example. Suitable for students in arts management programs as well, this book introduces readers to case-based learning via practical examples that give students insight into strategic decision-making in the creative industries"--